Crossing International and Research Boundaries: From Subject to Author for an Authentic Refugee Portrait. (16th February 2012) - Besic, Jasenka; McBrien, J. Lynn
Abstract : Scholars in training, including qualitative researchers, are often cautioned about their relationship to their research participants with the notion that "getting too close" can distort findings. However, with many participants, especially those with whom issues of trust are problematic due to their personal experiences, researchers cannot gain rich data without creating an authentic and close relationship. In this longitudinal study, a female Bosnian youth and an academic researcher grapple with issues of trust, friendship, and research in an effort to determine ways to create valid research findings over years of relationship building.